PRODUKSI ANTIBODI POLIKLONAL SUGARCANE STREAK MOSAIC VIRUS - Cahyo Artho Nugroho; Nur Basuki; Arifin Noor Sugiharto (BUANA SAINS, 2015)
Sugarcane Streak Mosaic is an important disease in sugarcane caused by Sugarcane streak mosaic virus (SCSMV). SCSMV attack intensity at the sample location sugarcane crop may reach 62%. The high intensity of the attack on the planting of sugar cane SCSMV make the virus should receive serious attention in order not widespread dissemination. One way to control the spread of the virus is the rapid detection. The rapid and precise mass detection to detect symptoms caused by the virus is by serologic testing. This study aims to produce polyclonal antiserum that can be used to detect SCSMV in sugarcane. Pure virus was analyzed using a spectrophotometer at a wavelength of 260 and 280 nm, a purity virus was 0.997. Pure virus particles injected into rabbits subcutaneously 3 times. Intake of rabbit blood serum performed 5 times and its IgG levels were measured by using a spectrophotometer nanodrop. The resulting antiserum is able to detect the presence of particles SCSMV on leaf tissue of sugarcane with the indication of the color change to yellow in wells ELISA Plate. Results of the process of reading absorbance at a wavelength of 405 nm by using ELISA reader machine showed a positive reaction because it shows the absorbance value is 3x greater than the negative control and the ratio between the sample is infected and a healthy sample or buffer (S/H Ratio)>2. Thus antiserum produced can be used as a detector SCSMV.